Financial and managerial aspects in human resource management : a practical guide - Pepple, Dennis; Zhang, Crystal (Emerald Publishing Limited, 2021)
Financial and Managerial Aspects in Human Resource Management: A Practical Guide explores both financial and management accounting and their links to human resource management decisions and practices.The book provides a pedagogic material that examines the fnanicial decisions that are specific to HR practices. Each chapter is mapped to CIPD and SHRM competency models and feature organisational examples, relevant case studies, critical theoretical discussions and end of chapter questions to give readers and learners a critical understanding of the following subjects: Introduction to financial accounting - Income statement and balance sheet - Interpretation of financial statements - Financial ethicsLearning and development cost - Redundancy - Disciplinary and grievance cost - Relocation cost - Family friendly policies - Executive compensation. Written for students and practitioners, this book breaks new ground by being the first to compile the everyday management and ficial decisions of HR managers in a single book. Financial and Managerial Aspects in Human Resource Management is an essential resource for understanding core practical HRM issues in the modern workplace.